Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Disiplin Kerja Pegawai Pada Dinas Perindustrian Dan Perdagangan Kabupaten Bima - Muhammad Akbar; Jaenab Jaenab (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to determine the influence of organizational culture and leadership style on employee work discipline at the Bima Regency Industry and Trade Service. The population in this study was 76 people and the sample used was 45 people with the sampling technique used in the research using type (saturated sampling). Data analysis takes the form of validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, correlation coefficient and determinant tests, t tests, and f tests. The research results obtained through the t test show that (1) the organizational culture variable (X1) has a positive and significant effect on work discipline (Y); (2) Leadership Variable (X2) has a positive and significant influence on employee performance (Y); (3) Leadership variables (X1) and organizational culture (X2) simultaneously (simultaneously) have a significant effect on work discipline.